Investigating the relationship between organizational intelligence and the performance of Melli Bank of Iran's South Branch Affairs Department - Rostami, Mehdi; Sanaei Dashti, Naser (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: The main purpose of the current research is to investigate the relationship between organizational intelligence and the performance of Melli Bank of Iran / South Tehran Branch Affairs Department employees. Methodology: The research method in this research is based on the objective of the applied type, based on the collection of information and analysis of the descriptive and non-experimental type, and in terms of the type of implementation of the survey. The statistical population of this research includes the employees of the South Tehran branch affairs department of the Melli Bank of Iran (about 110 branches) with 1128 employees, and 286 people were selected as a statistical sample using Cochran's formula. Two standard questionnaires of Albrecht's organizational intelligence and Robbins' organizational performance questionnaire were used to collect data. 18spss software was used to analyze the data, and the data were analyzed in two parts: descriptive and inferential statistics. Results: Kolmogorov-Smirnov test was used to check the distribution of data, and the results of this test with a significance level of less than 0.05 indicate the absence of normal distribution between the data. Also, using Spearman's correlation coefficient test, the relationship between organizational intelligence and employee performance was investigated. Conclusion: The research results showed that organizational intelligence directly affects employee performance.